If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 1 = -2(x + 2) Reorder the terms: 1 + y = -2(x + 2) Reorder the terms: 1 + y = -2(2 + x) 1 + y = (2 * -2 + x * -2) 1 + y = (-4 + -2x) Solving 1 + y = -4 + -2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + y = -4 + -1 + -2x Combine like terms: 1 + -1 = 0 0 + y = -4 + -1 + -2x y = -4 + -1 + -2x Combine like terms: -4 + -1 = -5 y = -5 + -2x Simplifying y = -5 + -2x
| 4y+15=6y-15 | | 4b+-6=-2 | | (5z+8)(z+4)=0 | | 3x+3=-3x-8 | | 3x-6x+6=x-7+13 | | 4v^2+8=200 | | e^3x-1=5e^2x | | 3x+3=-3y-8 | | y^2+y=6 | | 3/7w-11 | | 10x+(2x-4x)=32 | | 4x+2x-4=32 | | -x+2+x=22 | | y-6=-0.25(x+7.5) | | 5(3x-2)-5=5(x-2)+55 | | 2x-7=20-x | | -65π/36 | | 2(x)(x)-13x-7=0 | | 21=3/7w | | 7x^3-252x=0 | | 19x=5(x+3) | | 2/7x−5/6=-2/3 | | 8x+15=35 | | c^2=22c-104 | | 30x+4=25x+14 | | 43=15+x | | X^2-3x+6=5 | | 6-2(x+4)=13-2x | | 2(x=4)/3=12 | | x=435-(x-49) | | [9x+4]-11=-4 | | 2x+5(2x-1)=91 |